Influence of Content Marketing and Influencer Marketing on the Purchase Intention of Somethinc Products on TikTok Gen Z Users in Surabaya - Mila Kusuma Putri; Rizky Dermawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study investigates the impact of content marketing and influencer marketing on the purchase intention of Somethinc products among TikTok Gen Z users in Surabaya. The research employs quantitative methodology and smart PLS software, with 105 respondents from TikTok Indonesia users, aged 17–26, who saw product content featuring Sisca Kohl as an influencer on TikTok. The results show that content marketing has a positive influence and is significant against purchase intention, while influencer marketing has a positive influence and is significant against purchase intention.